Negotiating Global and Interdisciplinary Imperatives for Indigenous Education Scholarship and Pedagogy. Issue 2 (27th November 2015) - Charles, Harvey; Harris, Michelle; Carlson, Bronwyn
Abstract : Indigenous Studies is a rapidly growing field of enquiry both nationally and internationally. The internationalisation of the discipline is dependent on its interdiciplinarity and on the collaborative efforts of interdisciplinary scholars. Colonised Indigenous people globally share similar experiences despite differences in histories and contexts. In collaborative situations, dedicated scholarship brings together Indigenous people and allies who are committed to the global expansion of Indigenous knowledge through shared understandings of experiences and histories. Collective efforts can improve curriculum development, enhance opportunities for publication, bring scholars together in conferences and symposia and provide opportunities for new research networks for Indigenous scholarship. This paper addresses spheres of collaborative and collective endeavours that continue to reap benefits nationally and internationally in the field of international Indigenous Studies.